Focal application of low-dose-rate brachytherapy for prostate cancer: a pilot study - S. Sara Mahdavi; Ingrid T. Spadinger; Septimiu E. Salcudean; Piotr Kozlowski; Silvia D. Chang; Tony Ng; Julio Lobo; Guy Nir; Hamid Moradi; Michael Peacock; James Morris (Journal of Contemporary Brachytherapy, 2017)
Purpose: To evaluate the feasibility and to report the early outcomes of focal treatment of prostate cancer using low- dose-rate brachytherapy (LDR-PB). Material and methods: Seventeen patients were screened with multi-parametric magnetic resonance imaging (mpMRI), 14 of whom proceeded to receive trans-perineal template mapping biopsy (TTMB). Focal LDR-PB was performed on five eligible patients using dual air kerma strength treatment plans based on planning target volumes derived from cancer locations and determined by TTMB. Patient follow-up includes prostate specific antigen (PSA) measurements, urinary and sexual function questionnaires, repeated imaging and TTMB at specific intervals post-treatment. Results: Feasibility of focal LDR-PB was shown and short-term outcomes are promising. While the detection rate of tumors, a majority of which were low grade GS 3 + 3, was found to be low on mpMRI (sensitivity of 37.5%), our results suggest the potential of mpMRI in detecting the presence of higher grade (GS ≥ 3 + 4), and bilateral disease indicating its usefulness as a screening tool for focal LDR-PB. Conclusions : Low-dose-rate brachytherapy is a favorable ablation option for focal treatment of prostate cancer, requiring minimal modification to the standard (whole gland) LDR-PB treatment, and appears to have a more favorable side effect profile. Further investigation, in the form of a larger study, is needed to assess the methods used and the long-term outcomes of focal LDR-PB.